Mass balance of Trambau Glacier, Rolwaling region, Nepal Himalaya: in-situ observations, long-term reconstruction and mass-balance sensitivity - SOJIRO SUNAKO; KOJI FUJITA; AKIKO SAKAI; RIJAN B. KAYASTHA (Journal of Glaciology, 2019)
We conducted a mass-balance study of debris-free Trambau Glacier in the Rolwaling region, Nepal Himalaya, which is accessible to 6000 m a.s.l., to better understand mass-balance processes and the effect of precipitation on these processes on high-elevation Himalayan glaciers. Continuous in situ meteorological and mass-balance observations that spanned the three melt seasons from May 2016 are reported. An energy- and mass-balance model is also applied to evaluate its performance and sensitivity to various climatic conditions. Glacier-wide mass balances ranging from −0.34 ± 0.38 m w.e. in 2016 to −0.82 ± 0.53 m w.e. in 2017/18 are obtained by combining the observations with model results for the areas above the highest stake. The estimated long-term glacier mass balance, which is reconstructed using the ERA-Interim data calibrated with in situ data, is −0.65 ± 0.39 m w.e. a−1 for the 1980–2018 period. A significant correlation with annual precipitation (r = 0.77, p < 0.001) is observed, whereas there is no discernible correlation with summer mean air temperature. The results indicate the continuous mass loss of Trambau Glacier over the last four decades, which contrasts with the neighbouring Mera Glacier in balance.